A endometrial malignant tumor with yolk sac tumor component: a case report and literature review - Cui, Zicheng; Shan, Yuping; Chu, Huijun; Chen, Aiping (Frontiers in Oncology, 2025)
BackgroundPrimary endometrial yolk sac tumor (YST), as an extragonadal germ cell tumor, is an exceedingly rare malignancy characterized by high aggressiveness and poor prognosis. Currently, there is no standardized and effective treatment.Case reportWe report a case of a 71-year-old woman with primary mixed endometrial yolk sac tumor. She presented with postmenopausal vaginal bleeding. PET CT imaging suggested a uterine malignancy. Serum levels of AFP, CEA, and CA19–9 were elevated. Diagnostic endometrial biopsy pathology showed adenocarcinoma, suggestive of endometrioid carcinoma. The patient underwent laparoscopic extra-fascial total hysterectomy, bilateral salpingo-oophorectomy, right pelvic lymphadenectomy, and para-aortic lymph node biopsy. Postoperative pathology revealed mixed endometrioid carcinoma, within which a component exhibited features consistent with differentiation towards yolk sac tumor (YST). Immunohistochemistry showed focal AFP positivity (+), SALL4 positivity (+), and GPC3 positivity (+). Postoperatively, she received three cycles of BEP chemotherapy (bleomycin, etoposide, cisplatin), followed by concurrent chemoradiotherapy. Subsequently, she received one cycle of PEB chemotherapy. One month after completing chemotherapy, a PET-CT scan revealed a new lesion in the omentum, indicating disease recurrence. The patient opted for observation. On April 7, 2025, a follow-up chest CT showed multiple small pulmonary nodules, suggestive of metastases. Repeat AFP levels remained within the normal range. She is currently receiving combination therapy with paclitaxel, carboplatin, and pembrolizumab.ConclusionPrimary endometrial YST is an exceptionally rare malignant germ cell tumor. Early symptoms frequently include vaginal bleeding and abdominal pain, often accompanied by elevated serum AFP levels. Immunohistochemical markers such as AFP, GPC-3, SALL-4, and Villin are valuable for differentiating it from other entities. Advanced FIGO stage and age over 50 years were significantly associated with a higher likelihood of recurrence or death in our case and the available literature. Compared to pure endometrial YST, mixed endometrial YST occurs at an older age and appears to carry a worse prognosis. The currently most treatment for YST is radical surgical resection followed by adjuvant chemotherapy, typically the BEP regimen. The role of radiotherapy in improving outcomes requires further investigation.